The usage of sexual internet media and sexual behaviour among sexually experienced adolescents in Malaysia: sexual intention as a mediator - Tan, Soon Aun; Yaacob, Siti Nor; Tan, Jo Pei (Universiti Putra Malaysia Press, 2018)
This study examines the relationships between the use of sexually explicit material, sexual intention, and sexual behaviour in a sample of 189 sexually experienced adolescents (aged 16-17) in Malaysia. Additionally, this study investigates the mediating role of sexual intention on the relationship between the use of Sexual Explicit Internet Media (SEIM) and sexual behaviour. A self-administered questionnaire focusing on the use of SEIM scale, Youth Pre-coital and Sexual Intentions Scale, and Sexual Behaviour Assessment measured adolescents' use of SEIM, sexual intention, and sexual behaviour. The results demonstrate that the use of SEIM positively correlates with adolescents' sexual intention and sexual behaviour. Increasing engagements in sexually-related behaviour reveal an increase in sexual intentions. Findings also denote that higher exposure to SEIM promotes sexual intention, which in turn increases engagement in sexually-related behaviour. In the attempt to control sexual arousal among adolescents, prevention and intervention programmes which deal with sexuality should consider the role of Internet media and the development of healthy cognitive processes.